2014
DOI: 10.1093/her/cyu009
|View full text |Cite
|
Sign up to set email alerts
|

Health improvement for men and hard-to-engage-men delivered in English Premier League football clubs

Abstract: Unhealthy behaviours represent modifiable causes of non-communicable disease. In men, concern focuses on those (i) demonstrating the poorest health, exacerbated by a lack of awareness of the risks that their lifestyles pose and (ii) who neither consult their doctor nor use health services. Classed as 'hard-to-engage', distinctive strategies are needed to reach these men. Impact and process evaluations assessed the effect of a programme of men's health-delivered in/by English Premier League football clubs. Men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(97 citation statements)
references
References 29 publications
3
89
1
4
Order By: Relevance
“…Further, men including, older males demonstrated statistically significant improvements for a range of cardiovascular disease (CVD) risk factors. 41 Importantly, some participants reported that they did not engage in health improvement interventions led and delivered in traditional healthcare settings. 42 These two examples demonstrate the potential of football-based, PA-led health-improvement programmes for reaching and facilitating changes in the health behaviours of OA.…”
Section: Introductionmentioning
confidence: 99%
“…Further, men including, older males demonstrated statistically significant improvements for a range of cardiovascular disease (CVD) risk factors. 41 Importantly, some participants reported that they did not engage in health improvement interventions led and delivered in traditional healthcare settings. 42 These two examples demonstrate the potential of football-based, PA-led health-improvement programmes for reaching and facilitating changes in the health behaviours of OA.…”
Section: Introductionmentioning
confidence: 99%
“…BACT is the community arm and registered charity of Burton Albion Football Club, a professional football club. The authors have developed a range of health improvement based research projects over several years with BACT (Parnell, Hargreaves, et al, 2014;Pringle et al, 2014).…”
Section: Burton Albion Community Trust: Albion 2 Engage (2014)mentioning
confidence: 99%
“…A measure of quality of life was taken given the breadth of associated factors that appear to contribute to ASB. Finally, demographic profiles (including age, gender, ethnicity and post-code) and affiliation to football and/or football clubs (i.e., football fan, non-fan, fan of host club) were collected which aligned with previous research in football and social change contexts Pringle et al, 2014). The evaluation outlined above is the self-report approach to data collection via an online survey (university commissioned version of Google documents) based on past research on football interventions .…”
Section: Evaluation Planningmentioning
confidence: 99%
See 2 more Smart Citations